Investigação da perda de heterozigozidade em 9p, 9q e 17p e de mutações somáticas do TP53 em queilite actínica e carcinoma de células escamosas de lábio - Gefter Thiago Batista Correa (2015)
Objectives: Lip squamous cell carcinoma (LSCC) and actinic cheilitis (AC) molecular pathogenesis is unclear. We aimed to assess loss of heterozygostity (LOH) and TP53 mutations in these lesions. Materials and Methods: Formalin fixed paraffin-embedded (FFPE) samples of 17 LSCC and 16 AC were included. 5 fresh LSCC were added for the TP53 sequencing. We assessed LOH by using 6 polymorphic markers located at 9p22, 9q22 and 17p13 and associated these results with cell proliferation (Ki-67) and P53 immunostaining. Direct sequencing of TP53 exons 211 was performed in the fresh samples, and exons 5-9 in the FFPE. Results: LOH occurred in at least one marker in 15/17 LSCC and in 9/16 AC. The marker that showed higher frequency of allelic loss (FAL) in LSCC was D9S157 (8/12 informative cases), and D9S287 in AC (4/11 informative cases). IHC results were not associated with LOH or with the FAL. We found TP53 missense mutations in both lesions and nonsense in LSCC, including CC>TT transition, which is an UV signature. Conclusion: LOH and TP53 mutations occurred in LSCC and AC, which may be part of their molecular pathogenesis.